Narrativism Quarrel Revisited: Can Inquiry Revive the Narrative? - Řídký, Josef (Dějiny – teorie – kritika, 2019)
This paper investigates the narrativist debate on the nature of history and presents a review of some of its most significant contributors through the prism of concepts of ‘narration’ and ‘inquiry’. Since the main issue on which narrativist theoreticians and defenders of the historians’ craft disagree is their view on whether language is the source or merely a tool of history, this text investigates the role and importance the two parties ascribe to the layers of critical inquiry and narration. The paper focuses mainly on the writings of Hayden White and Paul Ricoeur, while also briefly commenting on the crucial theoretical works of Franklin Ankersmit, Hans Kellner, Philippe Carrard, and Ivan Jablonka. While White is often considered to be the main proponent of narrativists, it turns out that his approach to the subject was more nuanced than often thought and that it evolved over time. Paul Ricoeur, on the other hand, tends to view inquiry as a sort of poetic act and narration as an essential part of historical understanding.